PENGARUH EDUKASI MELALUI MEDIA FLIPCHART DIGITAL TERHADAP PENGETAHUAN SISWA TENTANG PENTINGNYA KONSUMSI BUAH DAN SAYUR (Jurnal Kesehatan Siliwangi, 2023)
The school period is the most rapid growth period after toddlerhood. One of the nutritional problems for school-age children is the lack of fruit and vegetable consumption. Therefore, it is necessary to provide health education about the importance of consuming fruits and vegetables in children. elementary school students through digital flipchart media.Purpose: To determine the effect of education through digital flipchart media on student’s knowledge about the importance of fruit and vegetable consumption. Methods: The research method used in this study was a quasi-experimental research design with one group pretest-posttest without control. With a subject of 80 respondents who came from students in grades 3, 4, and 5. Data analysis used Paired T-test to prove the research hypothesis. Results: The average score of respondents' knowledge before being given education through digital flipchart media was 69,28. The average knowledge of respondents after being given education through digital flipcharts is 88,84. The percentage increase in knowledge is 28,23%. The p-value of respondents' knowledge before and after being given education was (p = 0.000). Conclusion: There was a significant increase in knowledge after being given education through digital flipchart media on the importance of fruit and vegetable consumption.